Periodontal disease in smokers - Cerović Olivera; Bundalo Vera (Serbian Medical Society - Dental Section, Belgrade, 2005)
Tobacco contains about 4000 different toxic substances from which almost 40 are proven to be cancerogenic. Nicotine, toxic alkaloid, is the most active substance in tobacco causing major number of harmful consequences for human organism as a whole, and for periodontal tissues as well. The aim of the paper was to show harmful effects of smoking on periodontal disease development, and to point out the problems caused by smoking during and after the periodontal treatment. Periodontal disease occurs in smokers more frequently as opposed to non-smokers. Typically, smokers have lower level of gingival inflammation, more excessive and accelerated loss of alveolar bone and epithelial insertion, deeper periodontal pockets and numerous gingival recessions. Along with that, smokers are carrying a decreased immune response that is expressed through various defense mechanisms. Smoking has negative impact on the outcome of conservative and surgical periodontal therapy. Effects of smoking on periodontal therapy success rate are requiring administration of antiseptic solutions and antibiotics throughout the treatment course. Every periodontologist must influence patients to stop smoking and thus act preventively on occurrence and progress of periodontal disease.